Low rates of organ donation and transplantation : causes and solutions - Dimo, Peter M.; Mulqueeny, Delarise M. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Organ donation presents as a global public health, societal and educational challenge with a high number of patients with end-stage diseases being left in limbo due to the low rates of life-saving organ donation and transplantation. Organ transplantation is a definitive therapy for patients suffering from a wide range of end-stage diseases and organ failures which prolongs and improves their lives and wellbeing. Countries including South Africa struggle with low rates of organ donation and transplantation with the number of patients on organ donation waiting lists exceeding the number of available organs. Hence, the imbalance of organ supply and demand results in many patients dying prior to receiving life-saving organs. South Africa currently utilizes the opt-in system which assumes that all people do not want to be organ donors. This study’s aim sought to explore and assess factors responsible for low rates of organ donations with its aim being achieved through the employment of a qualitative approach aligned to an explorative research design. Additionally, the eco-systems theory was adopted as the theoretical framework for this study. Purposive sampling was used to recruit thirty research participants. In-depths interviews with traditional leaders in rural areas who were 20 years and older were used to collect data that was later analyzed using a thematic content approach. The study findings highlighted the breeding grounds for low rates of organ donation and transplantation. These include the refusal to grant consent for organ donation, lack of knowledge surrounding the process, pursuance of the opt-in system of organ donation, attitudes and socio-cultural factors contributing to the chronic shortage of life-saving organs. Moreover, recommendations emanating from the findings could improve the rate of organ donation and transplantation.